Inhibition of Kv1.3 channel restrains macrophage M2 polarization and ameliorates renal fibrosis via regulating STAT6 phosphorylation - Yanshan Chen; Yuanxing Zhi; Hailin Zhong; Liang Ma; Xinpei Gu; Yijing Cai; Jingjing Huang; Xin Yi; Xiaoyan Wu; Ken Kin Lam Yung; Pingzheng Zhou (Pharmacological Research)
Macrophages play crucial roles in regulating both homeostatic and inflammatory responses, with classical activated (M1) and alternatively activated (M2) subsets defined by the surrounding micro-environment. Renal fibrosis, developed from persistent inflammation, is worsened by M2 macrophages, yet the precise mechanisms underlying macrophage M2 polarization remain unclear. In this study, we investigated the role of Kv1.3, one of the primary potassium channels which is expressed in both innate and adaptive immunity, on macrophage M2 polarization and renal fibrosis. Our findings demonstrated that genetic or pharmacological inhibition of Kv1.3 significantly suppressed the expression of M2 markers and STAT6 phosphorylation. Furthermore, pharmacological inhibition of Kv1.3 by PAP-1 attenuated renal inflammation and fibrosis with decreased infiltration of macrophage infiltration and M2 polarization by employing the unilateral ureteral obstruction (UUO) renal fibrosis model. Mechanistically, we revealed that Kv1.3 was required for STAT6 phosphorylation in a mitochondria membrane potential dependent manner. Collectively, this study suggests that Kv1.3 is essential for macrophage M2 polarization and highlights the potential of Kv1.3 blockers as therapeutic agents for renal fibrosis and other M2 polarization-related diseases.